The establishment of an intermodal walkability index for use in car oriented urban environments: The case of Nicosia - Mouzas, Antony John; Ioannou, Byron; Fokaides, Paris (Frontiers in Environmental Science, 2022)
Sustainable mobility has been considered key in the pursuit of sustainable development in urban environments. This case study review focuses on Nicosia, a car-oriented, medium-sized city, and attempts to define an intermodal walkability index for the city center. In a city like Nicosia where more than 90% of the daily trips are done completely by car, encouraging intermodal mobility with walking as part of the trip is an important first step to sustainable mobility. The aim of the paper is to present a model based upon the most impactful sustainability indicators when referring to pedestrian mobility, and therefore will create an intermodal walkability index for grading the walkability of an urban environment, in our case a particular, car-oriented one. The index was developed by using the latest version of pyQGIS, due to the fact that the algorithms that are being used in the calculation of this index are already part of the geospatial analysis toolbox contained within QGIS. The paper uses as a case study the municipality of Nicosia in Cyprus where it was proven that pedestrian transportation can be graded in terms of walkability from the private car drop point. The study has also discovered that the use of primary electricity generation and fossil fuels for transport can be reduced if problematic areas that have a low or negative sustainability score are managed in ways that will increase the score.